Oxidation state of subarc mantle - Evans, Katy; Elburg, M.; Kamenetsky, V. (Geological Society of America, 2012)
The subarc mantle is a primary control on the composition of arc magmas and the formation of arc-related ore deposits. Elevated ferric iron contents in arc lavas have been interpreted as a record of subarc mantle that is oxidized relative to mid-oceanic ridge basalt (MORB), but this conclusion is controversial. Measurements of spinel compositions in primitive arc lavas imply an arc magma source 1–4 log units more oxidized than MORB and ocean island basalts analyzed using the same technique. Samples from seven arcs show a significant correlation (P < 0.0005) between redox budget, subduction zone convergence rate, and subduction zone age. These results support the notion of oxidized arc lavas in the mantle source zone, but resolution of contradictory evidence regarding subarc mantle redox state requires further work.